Electrochemical skin conductances values and clinical factors affecting sudomotor dysfunction in patients with prediabetes, type 1 diabetes, and type 2 diabetes: A single center experience - Calikoglu, Bedia Fulya; Celik, Selda; Idiz, Cemile; Bagdemir, Elif; Issever, Halim; Calvet, Jean-Henri; Satman, Ilhan (Primary care diabetes, 2023)
Sudomotor dysfunction is linked to small fibers damage. We investigated sudomotor dysfunction in a large group of participants with diabetes, prediabetes, and nondiabetic healthy subjects. This study aimed to complete knowledge on sudomotor dysfunction in this population, especially regarding the threshold values for the electrochemical skin conductance (ESC) and factors affecting it. A total of 690 volunteers in four groups were included in the study (type 1 [T1DG]: n = 80, 61.3% women; type 2 diabetes [T2DG]: n = 438, 63.5% women; prediabetes [Pre-DG]: n = 88, 80.7% women; healthy control [HC-G]: n = 84, 67.5% women). All subjects were investigated for clinical diabetic peripheral polyneuropathy and sudomotor dysfunction. The characteristics of participants obtained from outpatient records were evaluated. We used the Sudoscan device to measure ESC which was normalized for BMI, to improve the discriminative capability of the method. Diabetic polyneuropathy was found in 17.5% of T1DG, 27.4% of T1DG, and 10.2% of Pre-DG. The mean ESC/BMI was lower in subgroups with diabetic polyneuropathy than those without. Mean ESC/BMI was lowest in T2DG and highest in HC-G but comparable in T1DG and Pre-DG. We accepted the “mean ESC/BMI-1 SD” in the HC-G as the threshold for sudomotor dysfunction. Accordingly, the prevalence of sudomotor dysfunction was 18.8%, 44.3%, 59.1%, and 15% in T1DG, T2DG, Pre-DG, and HC-G, respectively. In T2DG, sudomotor dysfunction was found in 66.7% of persons with retinopathy, of which 56.3% had clinical diabetic polyneuropathy. The prevalence of sudomotor dysfunction in subjects with peripheral artery disease, chronic kidney disease, cardiovascular disease, and hypertension was 46.7%, 47.4%, 43.4%, and 50%, respectively, and 42.9%, 38.9%, 45.5%, and 37.3% of whom in the same order detected with clinical diabetic polyneuropathy. Considering the entire group, a logistic regression model demonstrated that the variables associated with SMD were: retinopathy (OR: 2.969; 95% CI: 1.723, 5.114), female gender (OR: 1.952; 95% CI: 1.287, 2.962), and e-GFR (OR: 0.989; 95% CI: 0.981, 0.998). Since the rate of complications was very low in T1DG, excluding this group, a new model similarly revealed that retinopathy and female gender were associated with SMD, however, the association with e-GFR was disappeared. The prevalence of sudomotor dysfunction is high when established peripheral polyneuropathy was present in diabetes. Even though, sudomotor dysfunction can also occur before clinical polyneuropathy in both types of diabetes (T1DG: 18.8%, T2DG 44.3%), prediabetes (59.1%), and nondiabetic healthy subjects (15%). The variables associated with sudomotor dysfunction were retinopathy and female sex. Normalization of ESC for BMI would be a beneficial approach. However, before this method is included in the routine screening programs for diabetic polyneuropathy, large-scale and prospective studies are required to reach a consensus on the pathological threshold values. •Raw ESC values are affected by age, gender and BMI values; It decreases with age and BMI, and is lower in women.•Raw ESC values can be misleading in revealing the presence of SMD; adjusted values for BMI give more meaningful results.•More work is needed to establish a universal ESC cut-off algorithm for SMD diagnosis.